Examining the Impact of Porphyromonas gingivalis Infection on Ovarian Health: A Reduction in Primordial Follicles in a Female Periodontitis Model - Meilawaty, Zahara; Galau, Argha Sirna; Permatasari, Sabania Dinar; Setyaningsih, Sari; Astuti, Pudji; Setiawatie, Ernie Maduratna; Hendarto, Hendy; Suci Dharmayanti, Agustin Wulan (Jurnal Kesehatan Gigi, 2025)
Periodontitis is a chronic inflammation of the periodontal tissues caused by periodontal pathogens, such as Porphyromonas gingivalis (P. gingivalis). P. gingivalis possesses several virulence factors that enable it to invade and spread through the bloodstream to other organs, including the ovaries. It triggers inflammation, which may impact the number of primordial follicles. The aim of this study was to assess the effects of P. gingivalis infection on the number of primordial follicles in the ovaries. This study was a laboratory experiment with a post-test control group design. The rats were divided into control and periodontitis groups. The periodontitis group consisted of rats induced with P. gingivalis in their sulcus gingiva of the first mandible molar every three days for 19 days. Therefore, control groups were without P. gingivalis induction. Seven days after the last induction of P. gingivalis, the rats were euthanized, and their ovarian tissues were collected for histological preparation. The primordial follicles were counted under 400x magnification. The results indicated that the treatment group had a significantly lower number of primordial follicles (2.2 Â± 2.61) compared to the control group (12.4 Â± 2.41). The study concludes that P. gingivalis infection led to a reduction in the number of ovarian primordial follicles in periodontitis models.